Temperature and heating induced temperature difference measurements from SIMBA-type sea ice mass balance buoy 2020T76, deployed during MOSAiC 2019/20 - Ruibo Lei; Jennifer K Hutchings; Mario Hoppmann; Zhuoli Yuan (PANGAEA, 2022)
Temperature and heating-induced temperature differences were measured along a chain of thermistors. SIMBA 2020T76(a.k.a. PRIC_10_04, IRIDIUM number 300234068528490) is an autonomous instrument that was installed on drifting sea ice in the Arctic Ocean during the 3rd leg of the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) in April 2020. The buoy was deployed at the site about 2 km from the ship with initial thicknesses of snow and ice of 0.14 and 150 m, respectively, on 4 April 2020. The thermistor chain was 5 m long and included 241 sensors with a regular spacing of 2 cm. The depths for the sensors are 72 to -406 cm, referring to the initial interface between snow and ice. The last sensor was used to measure the air temperature at 1 m above the initial snow surface. The resulting time series describes the evolution of temperature and temperature differences after two heating cycles of 30 and 120 s as a function of depth and time between 4 April 2020 and 20 July 2020 in sample intervals of 6 hours for temperature and 24 hours for temperature differences. In addition to temperature, geographic position, barometric pressure, tilt and compass were measured.